Characteristics of drug overdose suicide attempts presenting to the psychiatric emergency department of Beijing Anding Hospital - Lihui Tu; Yi Liu; Hui Zhu; Qinge Zhang; Xiao Ji (BMC, 2024)
Abstract Background Overdose-related suicide attempts represent a significant portion of self-harm presentations in the psychiatric emergency department (ED). Identifying specific patient characteristics associated with these attempts holds promise for pinpointing drug classes with elevated risk and paving the way for tailored suicide prevention interventions. This study aims to examine the demographic profiles of ED patients who had experienced overdose-related suicide attempts. Methods This retrospective study was conducted at Beijing Anding Hospital, Capital Medical University, from January 2020 to December 2021. Patients with psychiatric drug overdose suicide attempts presenting to the psychiatric ED were included. Sociodemographic characteristics and the specific classes of drugs involved were collected, and analysed descriptively. Results This study examined 252 overdose patients, excluding 51 patients treated with alcohol or nonpsychiatric drugs, and a total 201 cases were included. The mean age of the patients was 28 ± 16 years (median 23, range 12-78), and 82% (n = 165) of the sample were females. Notably, nearly half (45%) of the patients were aged ≤ 20 years. While the number of cases decreased with increasing age, a significant increase was observed in 2021 compared to 2020. Benzodiazepines (BZDs) were the most frequently implicated substance class (n = 126, 63%), followed by antidepressants (n = 96, 48%), antipsychotics (n = 44, 22%), Z-drugs (n = 43, 21%), and mood stabilizers (n = 36, 18%). For adolescents, antidepressants (n = 52, 71%) overtook BZDs (n = 38, 52%) as the most common drug. The monthly distribution of cases revealed peaks in April and November. Furthermore, 21% (n = 42) of patients ingested more than two psychotropic medications concurrently. Finally, approximately half (n = 92) of the patients required inpatient admission for further treatment. Comparisons between hospitalized and nonhospitalized patients did not reveal any significant differences. Conclusions The present study revealed a greater prevalence of suicide overdose attempts among young females receiving prescriptions for antidepressants and/or BZDs. This finding suggests a potential need for enhanced monitoring of suicidal behaviour in this specific population when prescribing psychotropic medications. These findings contribute to the growing body of knowledge regarding drug overdose suicide attempts in psychiatric emergency settings and underscore the importance of further research to develop targeted prevention interventions.